Effects of Phytophthora Inoculations on Photosynthetic Behaviour and Induced Defence Responses of Plant Volatiles in Field-Grown Hybrid Poplar Tolerant to Bark Canker Disease - Jaroslav Ďurkovič (MDPI AG, 2021)
Bark cankers accompanied by symptoms of decline and dieback are the result of a destructive disease caused by Phytophthora infections in woody plants. Pathogenicity, gas exchange, chlorophyll a fluorescence, and volatile responses to P. cactorum and P. plurivora inoculations were studied in field-grown 10-year-old hybrid poplar plants. The most stressful effects of P. cactorum on photosynthetic behaviour were found at days 30 and 38 post-inoculation (p.-i.), whereas major disturbances induced by P. plurivora were identified at day 30 p.-i. and also belatedly at day 52 p.-i. The spectrum of volatile organic compounds emitted at day 98 p.-i. was richer than that at day 9 p.-i, and the emissions of both sesquiterpenes α-cubebene and germacrene D were induced solely by the Phytophthora inoculations. Significant positive relationships were found between both the axial and the tangential development of bark cankers and the emissions of α-cubebene and β-caryophyllene, respectively. These results show that both α-cubebene and germacrene D are signal molecules for the suppression of Phytophthora hyphae spread from necrotic sites of the bark to healthy living tissues. Four years following inoculations, for the majority of the inoculated plants, the callus tissue had already closed over the bark cankers.